25 Jahre Maastrichter Verträge: Reale Divergenzen und institutionelle Reformen - Thomas Jost; Stefan Reitz (Wirtschaftsdienst, 2017)
25 Jahre nach Abschluss des Maastricht-Vertrages gibt es durchaus Zweifel an dessen Erfolg. Die Autoren zeigen auf, dass nur die Kernländer der Europäischen Wirtschafts- und Währungsunion eine dauerhafte Konvergenz ihrer wirtschaftlichen Entwicklung erlebten. Daher halten sie die gemeinsame Währungspolitik für verfehlt. Zudem werden Reformen, die auf eine intensivere Integration setzen, als kaum durchsetzbar angesehen. – – The paper argues that 18 years after the introduction of the Euro, the European Monetary Union has yet been unable to achieve sufficient real economic convergence among its member economies. As a result, the European Central Bank (ECB) still faces a dilemma in the sense that the common monetary policy is unable to meet current policy requirements in both boom and recession countries. Of course, the extensive asset purchase programmes of the ECB in the aftermath of the Euro crisis provided the necessary time for policy reforms, but deep rooted structural problems in a number of member countries and a divergent understanding of macroeconomic policy have remained and will lead to sustained high tensions in the eurozone in the foreseeable future.
Keywords: E52; E58; E62; 330